2001
DOI: 10.1038/sj.bmt.1703039
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone and cyclophosphamide: potential for enhanced lung toxicity

Abstract: Summary:Antineoplastic therapy can be associated with druginduced lung toxicity. With the increasing use of amiodarone for cardiac dysrhythmias there is an increasing possibility of its combined use with chemotherapies for various malignancies. We report a patient on long-term amiodarone who developed biopsy-proven druginduced lung toxicity after receiving high-dose cyclophosphamide, at a time-frame much shorter than would have been predicted with cyclophosphamide alone. The potential for enhanced lung toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Another case report describes accelerated pulmonary toxicity with the combination of cyclophosphamide plus amiodarone. 6 The frequency of cyclophosphamideinduced pulmonary toxicity is reported as approximately 1%. 1 This may be an underestimate, as it is difficult to diagnose cyclophosphamideinduced pulmonary toxicity when cyclophosphamide is used with other drugs that can cause lung injury or in the presence of pulmonary infections or malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another case report describes accelerated pulmonary toxicity with the combination of cyclophosphamide plus amiodarone. 6 The frequency of cyclophosphamideinduced pulmonary toxicity is reported as approximately 1%. 1 This may be an underestimate, as it is difficult to diagnose cyclophosphamideinduced pulmonary toxicity when cyclophosphamide is used with other drugs that can cause lung injury or in the presence of pulmonary infections or malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…It has the potential to cause pulmonary toxicity, most commonly in the form of diffuse alveolar damage. [1][2][3][4][5][6] Cyclophosphamideinduced pulmonary toxicity is extremely rare and often difficult to recognize because of presence of confounding factors, including use of other cytotoxic drugs, radiation pneumonitis, oxygen toxicity, pulmonary infections, and malignancies. Cyclophosphamide-induced pulmonary toxicity is accelerated when combined with amiodarone, an antiarrhythmic agent also capable of such toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 25 cases have been reported in the English literature since 1976 and two reviews have addressed those from 1967 to 1976 12,13 . Some reports were of patients with a second potential cause for interstitial pneumonitis such a second drug regime or an opportunistic infection 14–16 . The interval between the administration and the onset of respiratory symptoms is extremely variable, from a few weeks to 13 years after exposure 13,17–24 .…”
Section: Discussionmentioning
confidence: 99%
“…24 It has been suggested that the use of amiodarone to treat cardiac dysrhythmias in patients under chemotherapy could enhance potential chemotherapy-induced lung toxicity. 25 …”
Section: Treatmentmentioning
confidence: 97%